Patterns and determinants of prescribed drug use among pregnant women in Adigrat general hospital, northern Ethiopia: a cross-sectional study - Niguse Meles Alema; Getachew Semagn; Shetey Melesse; Ephrem Mebrahtu Araya; Hagazi Gebremedhin; Desalegn Getnet Demsie; Solomon Weldegebreal Asgedom; Etasy Weldekidan (BMC, 2020)
Abstract Background A vigilant prescription of drugs during pregnancy can potentially safeguard the growing fetus from the deleterious effect of the drug while attempting to manage the mother's health problems. There is a paucity of information about the drug utilization pattern in the area of investigation. Hence, this study was implemented to investigate the pattern of drug utilization and its associated factors among pregnant women in Adigrat general hospital, Northern Ethiopia. Methods An institution-based cross-sectional study was conducted among randomly selected 314 pregnant women who attended obstetrics-gynecology and antenatal care units of the hospital. Relevant data were retrieved from the pregnant women's medical records and registration logbook. The drugs prescribed were categorized based on the United States Food and Drug Administration (US-FDA) fetal harm classification system. Data analysis was done using SPSS version 20 statistical software. Multivariate logistic regression was employed to analyze the association of the explanatory variables with the medication use, and p < 0.05 was declared statistically significant. Results The overall prescribed drug use in this study was found to be 87.7%. A considerable percentage of the study participants (41.4%) were prescribed with supplemental drugs (iron folate being the most prescribed drug) followed by antibiotics (23.4%) and analgesics (9.2%). According to the US-FDA drug's risk classification, 42.5, 37, 13, and 7% of the drugs prescribed were from categories A, B, C, and D or X respectively. Prescribed drug use was more likely among pregnant women who completed primary [AOR = 5.34, 95% CI (1.53-18.6)] and secondary education [AOR = 4.1, 95% CI (1.16-14)], who had a history of chronic illness [AOR = 7.9, 95% CI (3.14-19.94)] and among multigravida women [AOR = 2.9, 95% CI (1.57 5.45)]. Conclusions The finding of this study revealed that a substantial proportion of pregnant women received drugs with potential harm to the mother and fetus. Reasonably, notifying health practitioners to rely on up-to-date treatment guidelines strictly is highly demanded. Moreover, counseling and educating pregnant women on the safe and appropriate use of medications during pregnancy are crucial to mitigate the burden that the mother and the growing fetus could face.